Analysis of Learning Difficulties of Students Class XI in Chemistry Subjects - Hikma, Hikma; Suherman, Suherman (Jurnal Akademika Kimia, 2023)
This study aimed to determine (1) the internal factors that cause learning difficulties in chemistry subjects for students of class XI MIA SMA Negeri 1 Tinombo Selatan, including attitudes towards learning, motivation, interest, and health; (2) the external factors that cause learning difficulties for class XI students of SMA Negeri 1 Tinombo Selatan include family, school, and community environment. This research was descriptive. The research subjects were 92 students. The collection technique used a questionnaire on the factors of learning difficulties. The data analysis technique used was descriptive with a percentage. The results showed that (1) the internal factors that caused learning difficulties were as follows: the attitude indicator towards learning was 16.44 %, the motivation indicator was 13.45 %, the interest indicator was 18.26 %, and the health indicator was 18.88 %. (2) External factors that cause learning difficulties are the family indicator was 23.23 %, the school indicator was 87.77 %, while the community indicator was 25.16 %.